Multiresidues Multiclass Analytical Methods for Determination of Antibiotics in Animal Origin Food: A Critical Analysis - Sílvia Cruz Barros; Ana Sanches Silva; Duarte Torres (MDPI AG, 2023)
Veterinary drugs are widely used to prevent and treat diseases. The European Union has forbidden the use of antibiotics as growth promoters since 2006. Its abusive use leads to the presence of antibiotic residues (AR) in foods of animal origin which is associated with antibiotic resistance. The monitoring of AR in food intended for human consumption is of utmost importance to assure Food Safety. A systematic bibliographic review was carried out on the analytical methodologies, published in 2013, for the determination of AR in foods of animal origin. The food processing effect in the AR detected in animal products is also addressed. However, there is a preference for multiresidues multiclass methods, i.e., methodologies that allow determining simultaneously different classes of antibiotics, which is still a challenge for researchers. The wide diversity of physico-chemical properties of these drugs is an obstacle to achieving excellent analytical performance for a vast number of molecules analyzed concurrently. New techniques in sample preparation continue to be developed in order to obtain a compromise between good recoveries and extracts without interferences (clean extracts). The most widely used analytical methodology for the determination of AR is liquid chromatography coupled with mass spectrometry. However, the current trend is focused on the use of powerful high-resolution MS detectors such as Time of Flight and Orbitrap with modern chromatographic systems. Cooking time and temperature control are the key processing conditions influencing the reduction of AR in foods.